Intelligent Soft Surgical Robots for Next‐Generation Minimally Invasive Surgery. (24th May 2021) - Zhu, Jiaqi; Lyu, Liangxiong; Xu, Yi; Liang, Huageng; Zhang, Xiaoping; Ding, Han; Wu, Zhigang
Abstract : Soft Surgical Robots In article number 2100011, Zhigang Wu and co‐workers provide a comprehensive overview on the emerging soft robotic technologies for minimally invasive surgery which are expected to redefine/expand current surgical robots and bring some exciting possibilities. The cover image demonstrates a high‐demanding scene of kidney stone lithotripsy, in which the soft surgical robot can be as gentle, biocompatible, powerful, and all‐pervasive as a plant.